Young Cassavapreneurs Indonesia: Strategi Pembelajaran Kewirausahaan “Lawang Lima Sampeureun Jaga” di Desa Benteng - Sultan Laga Putra Azdi; Maulida Nurul Fatkhiyatut Taufiqoh; Zakiyah Salsabila Syafhil; Flamora Gresafira Cahya; Sri Wiji Utami; Lindawati Kartika (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Young Cassavapreneurs Indonesia (YCPI) is a program that aims to address problems such as the utilization of cassava that is not yet optimal, the importance of instilling the spirit of creative entrepreneurship in youth, and low education of Benteng villagers. Benteng Village locates in Ciampea, Bogor District. The objectives of this program are 1) Increase the entrepreneurial knowledge, skills, and attitudes of students pursuing high school equivalency and open-school in Benteng Village; 2) Improve the economic value of cassava which is the potential commodity of Benteng Village, and 3) Establish a new small enterprise based on local wisdom. Primary sources of data are from interviews and questionnaires. The methods used are the House Model Horovitz and Ohlsson-Corboz and the Balanced Scorecard method. The House Model concept divided into three parts: specific goal and partnership (roof), Lawang Lima Sampeureun Jaga (middle), and the process of teaching and learning activities (foundation). Overall, the YCPI Program, which consists of 9 performance targets and 15 key indicators, has reached the target of 100%. Pretest, posttests, and also the evaluation of increasing knowledge, skills, and attitude of students are the factors of the successful YCPI program. The pre-test and post-test results showed the percentage of the learning outcomes of the participants ≥3 was 100% or there was an increase in the knowledge, skills, and attitudes of the students as a whole after the program ended.